2014
DOI: 10.1007/s00214-014-1538-x
|View full text |Cite
|
Sign up to set email alerts
|

Solvatochromic probe in molecular solvents: implicit versus explicit solvent model

Abstract: the ground and of the excited states of the molecule, and therefore, they induce shifts of the maxima in absorption or emission spectra. Two important factors contributing to the overall effect are the long-range electrostatic interactions with the solvent polarizing the solute and the shortrange contributions such as dispersion or specific solutesolvent interactions, e.g., hydrogen bonding. Properties of the solvent which affect the spectra of the solute are commonly described by empirical parameters quantify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 41 publications
1
54
0
Order By: Relevance
“…Given that a QM treatment of solvent might be desirable, the careful researcher may next wonder how much solvent should be treated quantum mechanically. A number of studies have explored this question for different molecular properties, and the study of convergence of excitation energies with increasing size of molecular environment has become an area of active research . Although in some systems a large amount of QM solvent may not be critical for accurately computing the property of interest, we have found that for excited states, values within approximately 0.05 eV of the converged value can be obtained with a full solvation shell treated with QM, as shown in Figure .…”
Section: Solvent Models For Excited State Calculationsmentioning
confidence: 85%
See 2 more Smart Citations
“…Given that a QM treatment of solvent might be desirable, the careful researcher may next wonder how much solvent should be treated quantum mechanically. A number of studies have explored this question for different molecular properties, and the study of convergence of excitation energies with increasing size of molecular environment has become an area of active research . Although in some systems a large amount of QM solvent may not be critical for accurately computing the property of interest, we have found that for excited states, values within approximately 0.05 eV of the converged value can be obtained with a full solvation shell treated with QM, as shown in Figure .…”
Section: Solvent Models For Excited State Calculationsmentioning
confidence: 85%
“…A number of studies have explored this question for different molecular properties, [61][62][63][64][65][66] and the study of convergence of excitation energies with increasing size of molecular environment has become an area of active research. [10][11][12][67][68][69] Although in some systems a large amount of QM solvent may not be critical for accurately computing the property of interest, we have found that for excited states, values within approximately 0.05 eV of the converged value can be obtained with a full solvation shell treated with QM, as shown in Figure 3. [13] The amount of solvent required for this level of accuracy was similar for both polar and less-polar solutes, although this was somewhat dependent on the choice of the electronic structure method.…”
Section: Combining Qm Explicit Solvent With Classical Solvent Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental/solvation effects are typically included in spectra calculations through continuum dielectric or quantum mechanics (QM)/molecular mechanics (MM) models. 40 , 43 45 These models are best suited for the description of isolated (spectrally distinct) chromophores ( e.g. dyes or aromatic amino acids) embedded in a solvent and/or protein medium.…”
Section: Methodsmentioning
confidence: 99%
“…This statement is one of the main components of solute-solvent interaction research strategy. Its further development has resulted in two solvent models: implicit (continuum) and explicit (discrete); their comparative effectiveness has been discussed in recent publications [78][79][80][81][82][83][84]. In this connection, the endohedral complexes of fullerenes and nanotubes can be viewed as a variety of explicit models.…”
Section: Introductionmentioning
confidence: 99%